-9h - 6 + 12h + 40 = 22.

h equals what?

Printable View

- December 12th 2005, 08:00 PMAmandaI need help solving this equation.
-9h - 6 + 12h + 40 = 22.

h equals what? - December 13th 2005, 03:55 AMctelady
-9h - 6 + 12h + 40 = 22. Combine on the left to simplify

12h-9h +40-6 = 22

3h +34 = 22 We need the part with the unknown on one side and the plain numbers on the other side. Since 34 is being added on the left, we must do the opposite thing. Subtract 34 from both sides.

Then we need the unknown to stand alone. Since h is being multiplied by 3, we must do the opposite thing. Divide both sides by 3. - December 13th 2005, 05:34 PMAmanda
Thank you ctelady.

- January 5th 2006, 03:03 PMmiss_lolittaexcuseme!!
The right answer of this question is

3h+34=22

3h=22-34

h=12/3

h=4 - January 5th 2006, 05:25 PMctelady
The right answer of this question is

3h+34=22

3h=22-34

h=12/3

h=4

There is a small, but important typo: 22-34 = -12

Divide that by 3 for the final answer. - January 5th 2006, 05:52 PMRich B.
Ahhh, so the quotient of a negative and positive is negative! You go Ctelady!

:)

...Rich B.